208 Compliance and Persistence to Grass Immunotherapy Treatment is Comparable for Allergy Immunotherapy Tablets and Subcutaneous Immunotherapy: A Swedish Registry Study - Andreasen, Jakob Nørgaard (World Allergy Organization Journal, 2012)
BACKGROUND: Allergy immunotherapy tablets (AITs) are administered by the patients in their homes and the medical compliance and persistence may therefore be poorer than for subcutaneous immunotherapy (SCIT) administered by physicians. Purpose: to compare medical compliance and persistence for AIT and SCIT treatments in Swedish patients with allergic rhinoconjunctivitis (ARC). METHODS: Two products for the treatment of grass pollen induced ARC were investigated: a SCIT treatment (Alutard SQ, Phleum pratense, 100,000 SQ-U/mL) and an AIT treatment (Grazax, Phleum pratense 75,000 SQ-T/2,800 BAU), ALK, Denmark). Data were drawn from the Prescribed Drug Registry 2007–2009, the National Board of Health and Welfare in Sweden. Data on patients treated and number of packages sold were used to calculate the compliance and persistence for each of the 2 products, for patients who started treatment in 2007. COMPLIANCE: calculated as the duration of treatment estimated from the number of packages sold (assuming 100% compliance), divided by the actual duration of treatment (the time estimated from the first to the last observed prescription, plus the duration of the last package). Persistence: calculated as the percentage of patients who continued their treatment in 2009 with at least initiation of 1 treatment package or vial in 2009. RESULTS: Grass AIT treatment was started by 636 patients and the grass SCIT treatment by 354 patients in 2007. The persistence of treatment in 2009 was 55% for grass AIT treatment and 57% for grass SCIT treatment. The estimated average duration of treatment was 2.34 years for grass AIT and 2.47 for grass SCIT at cut-off 31 December 2009. The average number of tablets used per patient during this period was 770. For grass SCIT treatment the average number of up-dosing kits used was 1.07 and the average number of maintenance vials was 3.26 (5 injections per vial). This corresponded to a compliance of 90% for grass AIT and 82% for grass SCIT. CONCLUSIONS: Compliance to treatment for grass ait and grass scit treatments were both high (>80%) and comparable. The persistence of swedish patients was comparable for grass AIT and grass SCIT treatments during the period 2007 to 2009.